The chloroplast proteome - Whitelegge, Julian (Henry Stewart Talks, 2007)
What is proteomics and what does it measure?, Protein identification by mass spectrometry, The problem of complex mixtures and protein identification, Quantitative proteomics and stable isotope labelling, Intact protein mass measurements and top-down proteomics Update talk: What is proteomics and what does it measure, Update talk: Top-down high-resolution FT-ICR mass spectrometry, Update talk: Characterization of thylakoid membrane, Update talk: Membrane proteins and lipids, Update talk: Lipid-protein complexes in gels, Update talk: PSI-ATP synthase supercomplex
Updated at 2021/10/31